Endoplasmic Reticulum Stress Plays a Key Role in the Pathogenesis of Diabetic Peripheral Neuropathy - Lupachyk, Sergey (American Diabetes Association, 2013)
Endoplasmic reticulum stress resulting from abnormal folding of newly synthesized proteins impairs metabolism, transcriptional regulation, and gene expression, and it is a key mechanism of cell injury. Endoplasmic reticulum stress plays an important role in cardiovascular and neurodegenerative diseases, cancer, and diabetes. We evaluated the role for this phenomenon in diabetic peripheral neuropathy. Endoplasmic reticulum stress manifest in upregulation of multiple components of unfolded protein response was identified in neural tissues (sciatic nerve, spinal cord) of streptozotocin diabetic rats and mice. A chemical chaperone, trimethylamine oxide, administered for 12 weeks after induction of diabetes (110 mg⋅kg(−1)⋅d(−1), a prevention paradigm) attenuated endoplasmic reticulum stress, peripheral nerve dysfunction, intraepidermal nerve fiber loss, and sciatic nerve and spinal cord oxidative-nitrative stress in streptozotocin diabetic rats. Similar effects on diabetes-induced endoplasmic reticulum stress and peripheral nerve dysfunction were observed with a structurally unrelated chemical chaperone, 4-phenylbutyric acid (100 mg⋅kg(−1)⋅d(−1), intraperitoneal). CCAAT/enhancer-binding protein homologous protein (CHOP)(−/−) mice made diabetic with streptozotocin displayed less severe sciatic nerve oxidative-nitrative stress and peripheral neuropathy than the wild-type (C57Bl6/J) mice. Neither chemical chaperones nor CHOP gene deficiency reduced diabetic hyperglycemia. Our findings reveal an important role of endoplasmic reticulum stress in the development of diabetic peripheral neuropathy and identify a potential new therapeutic target.